Detection of silver nanoparticles inside leaf of European beech (Fagus sylvatica L.) - Ballikaya, Paula; Mateos, José María; Brunner, Ivano; Kaech, Andres; Cherubini, Paolo (Frontiers in Environmental Science, 2023)
In a greenhouse experiment, silver nanoparticles (Ag-NPs) were applied on European beech (Fagus sylvatica L.) leaves using the droplet application method. Scanning electron microscopy (SEM) analyses showed that after 24 h Ag-NPs were mostly present in aggregates or as single particles on the surface of the leaf, surrounding or covering the stomata. Analyses of cross sections of the leaf revealed that some Ag-NPs were adhering to the cell walls of the mesophyll and palisade cells, most likely after penetration into the leaf through the stomata as particles and not as Ag ions. Our preliminary results showed evidence of foliar uptake of Ag-NPs in European beech. This opens new insights on the ability of trees to take up solid nanosized particles, eventually contained in raindrops, through their leaves, and potentially transport them to other parts of the tree. This study would be helpful for investigating the role of trees in atmospheric ultrafine particle mitigation.